2009
DOI: 10.1093/geronb/gbn004
|View full text |Cite
|
Sign up to set email alerts
|

Surprising SES Gradients in Mortality, Health, and Biomarkers in a Latin American Population of Adults

Abstract: BackgroundTo determine socioeconomic status (SES) gradients in the different dimensions of health among elderly Costa Ricans. Hypothesis: SES disparities in adult health are minimal in Costa Rican society.MethodsData from the Costa Rican Study on Longevity and Healthy Aging study: 8,000 elderly Costa Ricans to determine mortality in the period 2000–2007 and a subsample of 3,000 to determine prevalence of several health conditions and biomarkers from anthropometry and blood and urine specimens.ResultsThe ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 24 publications
9
112
3
10
Order By: Relevance
“…Earlier research has shown that in Costa Rica SES disparities in adult health are small, null, or even contrary to the expected negative SES gradients (17). This article systematically compares the SES gradients in adult mortality and health risk factors in newly compiled Costa Rican data with comparable data in the United States, namely the National Longitudinal Mortality Studies (NLMS) in the two countries, the Costa Rican Longevity and Healthy Aging Study (CRELES), and the US National Health and Nutrition Examination Survey (NHANES).…”
Section: Significancementioning
confidence: 88%
“…Earlier research has shown that in Costa Rica SES disparities in adult health are small, null, or even contrary to the expected negative SES gradients (17). This article systematically compares the SES gradients in adult mortality and health risk factors in newly compiled Costa Rican data with comparable data in the United States, namely the National Longitudinal Mortality Studies (NLMS) in the two countries, the Costa Rican Longevity and Healthy Aging Study (CRELES), and the US National Health and Nutrition Examination Survey (NHANES).…”
Section: Significancementioning
confidence: 88%
“…Better educated and wealthier individuals have sometimes higher rates of metabolic syndrome (8). However, less educated persons are generally more likely to display other risk factors (smoking, sedentary lifestyle, high fat diet, overweight) (9).…”
mentioning
confidence: 99%
“…Cabe señalar que se registraron puntuaciones medias y altas con respecto a las escalas que evaluaban percepción de apoyo en tres aspectos: a) apoyo familiar (con las personas con las que viven y familia extensa), b) amistades y c) ellas mismas como sujetos para otorgar apoyo a las demás personas (confianza). La mayoría de participantes conviven con su pareja e hijos, lo que habla de la conformación familiar tradicional en el esquema de vida de las personas adultas mayores residentes en Costa Rica (Fernández & Robles, 2006;Rosero-Bixby & Dow, 2009). …”
Section: Tabla 3 Descriptivos Variables Medidas Según Escalas E íNdicunclassified